Analisis Pengaruh Komunikasi Bisnis Digital terhadap Kepercayaan Konsumen di Waroeng Doloe - Desvika Anggraini Adrialno; Nadia Septiasa; Siti Nursima Arora; M. Naufal Muzakhi; Susriyanti, Susriyanti (CV. ITTC INDONESIA, 2026)
The development of digital technology has transformed the way companies interact with their customers, making digital business communication a key factor in building trust. This study aims to analyze the effect of digital business communication on consumer trust at Waroeng Doeloe. A quantitative approach was employed, with data collected through questionnaires distributed to consumers who interact via digital channels. The data were analyzed using simple linear regression. The results indicate that digital business communication has a positive and significant effect on consumer trust, particularly through efficient, transparent, and responsive communication.